Comparative analysis of 343 plastid genomes of Solanum section Petota: Insights into potato diversity, phylogeny, and species discrimination - Yan, L.; Zhu, Z.; Wang, P.; Fu, C.D.; Guan, X.; Kear, P.; Zhang, C.C.; Zhu, G.Y. (Wiley, 2023)
Common potato (Solanum tuberosum L.) and its wild relatives belong to Solanum section Petota. This section's phylogeny and species delimitation are complicated due to various ploidy levels, high heterozygosity, and frequent interspecific hybridization. Compared to the nuclear genome, the plastid genome is more conserved, has a haploid nature, and has a lower nucleotide substitution rate, providing informative alternative insights into the phylogenetic study of section Petota. Here, we analyzed 343 potato plastid genomes from 53 wild and four cultivated species. The diversity of sequences and genomes was comprehensively analyzed. A total of 24 species were placed in a phylogenetic tree based on genomic data for the first time. Overall, our results not only confirmed most existing clades and species boundaries inferred by nuclear evidence but also provided some distinctive species clade belonging and the maternally inherited evidence supporting the hybrid origin of some species. Furthermore, the divergence times between the major potato clades were estimated. In addition, the species discriminatory power of universal barcodes, nuclear ribosomal DNA, and whole and partial plastid genomes and their combinations were thoroughly evaluated; the plastid genome performed best but had limited discriminatory power for all survey species (40%). Overall, our study provided not only new insights into phylogeny and DNA barcoding of potato but also provided valuable genetic data resources for further systematical research of Petota.